(untitled) (Docentes 2.0 Journal, 2025)
The printing press has occupied a central place in human history, profoundly transforming how knowledge is produced, distributed, and consumed. The present study aimed to analyze the historical and pedagogical relevance of the printing press in the 21st century, exploring its integration into educommunicative processes as a strategy to strengthen professional communication training. Research was carried out within the framework of the pragmatic paradigm, the analytical-synthetic method, the mixed approach, the explanatory sequential design of a concurrent type, and the cross-sectional design. The sample was non-probabilistic and intentional, composed of 34 students from the Communication program at the Universidad Nacional de Loja, who developed practical workshops in printed newspaper production. Surveys were applied to gather their perceptions, and direct observation was conducted during the activities. The results revealed the value of working with printed newspapers despite the predominance of digital media. This medium fostered their understanding of the historical foundations of communication and promoted critical reflection on the bases of the communicative process. It also facilitated the development of creative skills. In conclusion, the printing press remains relevant in the training of communicators by connecting the historical roots of communication with contemporary practices and promoting key skills in professional performance.